2011
DOI: 10.1007/s00021-010-0047-5
|View full text |Cite
|
Sign up to set email alerts
|

The 3-D Inviscid Limit Result Under Slip Boundary Conditions. A Negative Answer

Abstract: We show that, in general, the solutions to the initial-boundary value problem for the Navier-Stokes equations under a widely adopted Navier-type slip boundary condition do not converge, as the viscosity goes to zero, to the solution of the Euler equations under the classical zero-flux boundary condition, and same smooth initial data, in any arbitrarily small neighborhood of the initial time. Convergence does not hold with respect to any space-topology which is sufficiently strong as to imply that the solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 6 publications
1
39
0
Order By: Relevance
“…The arbitrarily strong convergence results proved in [4], some estimates proved for non-flat boundaries in [2] and [3], and the strong convergence results available in the two-dimensional case, led to the conviction that strong convergence results held in the general three-dimensional case, at least in "moderately strong" topologies. In spite of this guess, in reference [5] we have shown that the result is false in a sphere.…”
Section: Introduction and Some Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The arbitrarily strong convergence results proved in [4], some estimates proved for non-flat boundaries in [2] and [3], and the strong convergence results available in the two-dimensional case, led to the conviction that strong convergence results held in the general three-dimensional case, at least in "moderately strong" topologies. In spite of this guess, in reference [5] we have shown that the result is false in a sphere.…”
Section: Introduction and Some Resultsmentioning
confidence: 95%
“…Recently the vanishing viscosity limit problem under the above or similar Navier type conditions has been studied in [2], [8], [12], [14], in the 2D case, and in [2], [3], [5], [7], [21], in the 3D case. See also [23] for the magnetohydrodynamic system and [6] for a different approach to the inviscid limit for the slip-type boundary value problem.…”
Section: Introduction and Some Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the case of slip without friction, it was shown in [12] that the boundary condition (3.4) is not necessarily preserved under the Euler evolution in three space dimensions if the boundary is not flat. The strong zero-viscosity limit does hold for free boundary conditions, hence for arbitrary smooth domains in two space dimensions, and for slip-without friction boundary conditions on domains with flat boundary [9,10,147,11]. In fact, only the initial data need to satisfy the stronger free condition at the boundary [14].…”
Section: Case Of Slip-type Boundary Conditionmentioning
confidence: 99%